2016
DOI: 10.1111/and.12635
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Gallic acid on doxorubicin-induced testicular and epididymal toxicity

Abstract: The effect of Gallic acid (GA) on doxorubicin (DOX)-induced testicular and epididymal toxicity was investigated in experimental rat model. The rats were randomly divided into six groups of 10 animals per group. Rats in group A received clean tap water ad libitum. Rats in group B were administered DOX intraperitoneally at 15 mg/kg on the eighth day of the experiment. Animals in groups C and D received 60 and 120 mg/kg GA orally for 7 days with 15 mg/kg DOX on the eighth day. Rats in groups E and F received 60 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 53 publications
5
24
0
Order By: Relevance
“…In fact, many studies shown that there was a decrease in epididymal sperm count in parallel with the decrease in testosterone level after DOX exposure. 47,62,65,68 In our study, we found a significant decrease in the levels of testosterone and epididymal sperm counts in DOX-treated groups in parallel with the literature. On the other hand, the fact that testosterone levels and epididymal sperm counts were significantly higher in the prophylaxis and treatment groups compared to the DOX group indicates that fluvastatin applied to these groups may have a protective effect on spermatogenesis in testicular toxicity after DOX exposure.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, many studies shown that there was a decrease in epididymal sperm count in parallel with the decrease in testosterone level after DOX exposure. 47,62,65,68 In our study, we found a significant decrease in the levels of testosterone and epididymal sperm counts in DOX-treated groups in parallel with the literature. On the other hand, the fact that testosterone levels and epididymal sperm counts were significantly higher in the prophylaxis and treatment groups compared to the DOX group indicates that fluvastatin applied to these groups may have a protective effect on spermatogenesis in testicular toxicity after DOX exposure.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, feeding diabetic rats 10 or 40 mg/kg of Vernonia cinerea L., plants, containing phytochemicals that include GA, improved number of spermatozoa, their motility and blood testosterone concentrations (Pomjunya et al, ). In other studies, GA (60 or 120 mg/kg for 7 or 14 d respectively) decreased percentage abnormal spermatozoa and reproductive toxicity in rats given anti‐cancer and anti‐neoplastic drugs, with concurrent increases in motility and viability of epididymal spermatozoa (Olusoji et al, ; Oyagbemi et al, ). However, in the present study, addition of CA to extender did not significantly improve motility of frozen‐thawed ram spermatozoa.…”
Section: Discussionmentioning
confidence: 83%
“…Our result showed that VC treatment could improve sperm concentration and motility, increase serum testosterone concentration, decrease the percentage of abnormal spermatozoa and restore the normal testicular structure. Previous studies have reported that some phytochemicals including gallic acid has the potential to protect against oxidative stress in the testes and to reversed sperm abnormalities [25, 34]. Another study showed that selenium had beneficial effects on male infertility, wherein it improved the sperm count and motility, increased serum testosterone levels and alleviated the histopathological changes in the testes [3, 32, 33].…”
Section: Discussionmentioning
confidence: 99%